(untitled) (Fiep Bulletin - online, 2014)
The acetabular labrum is a fibrocartilaginous rim. Labral tears normally presents symptoms like pain, click, and "giving way" sensation. The treatment for these injuries can be through by arthroscopic surgery or physical therapic approach. The objectives of rehabilitation are symptoms relief, to provide stability, proprioception and muscle imbalance. Plyometric training and sports activities are introduced in an advanced phase.